User experience of autism social-aid among autistic children: AUTISM social aid application - Azahari, I.N.N.A. (Springer Verlag, 2017)
Autism is a developmental disability that influences a significant number of daily skills, which includes social, communication and behavioural challenges. Technology has proven as one of the prompt intermediation and efficient educational method that leads to infinite improvement especially for children. Autistic children seem to have difficulties in communication and social skills and as a result of this need their teachers and parents’ support with their social interaction. Numerous educational practices and approaches have been carried out in order to assist as well as develop these children. This paper presents the results of user experience testing of Autism Social-Aid mobile application to children with autism. The session was conducted to children with medium functioning Autism Spectrum Disorder, from two different age groups that include 5–14 years old and 14–18 years old. The children’s reactions were observed and scored by a moderator. Results have shown that majority of the children with autism are more confident and satisfied when using the application. The application does need to be improved in ways that could capture the child’s attention towards the mobile activities. © Springer International Publishing AG 2017.